Interpretable Machine Learning Model Based on Superb Microvascular Imaging for Non-Invasive Determination of Crescent Status of IgAN - Tang Y; Liu X; Zhou W; Qin X (Dove Medical Press, 2024)
Yan Tang,1,* Xiaoling Liu,1,* Wang Zhou,2 Xiachuan Qin3 1Department of Ultrasound, Beijing Anzhen Hospital Nanchong Hospital, Nanchong Central Hospital, The Second Clinical Medical College, North Sichuan Medical College (University), Nan Chong, Sichuan, 637000, People's Republic of China; 2Department of Ultrasound, The First Affiliated hospital of Anhui medical University, Hefei, Anhui, 230022, People's Republic of China; 3Department of Ultrasound, Chengdu Second People's Hospital, Chengdu, Sichuan, 610000, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiachuan Qin, Department of Ultrasound,Chengdu Second People's Hospital,Chengdu, Sichuan, 610000, People's Republic of China, Tel +86 18113917878, Email 11326636@qq.comPurpose: To assess the crescentic status of IgA nephropathy (IgAN) non-invasively using a superb microvascular imaging (SMI)-based radiomics machine learning (ML) model.Patients and Methods: IgAN patients who underwent renal biopsy from June 2022 to October 2023, with two-dimensional ultrasound (US) and SMI examinations conducted one day prior to the renal biopsy. The patients selected were divided randomly into a training group and a test group in a 7:3 ratio. Radiomic features were extracted from US and SMI images, then radiomic features were constructed and ML models were further established using logistic regression (LR) and extreme gradient boosting (XGBoost)XGBoost to determine the crescentic status. The utility of the proposed model was evaluated using receiver operating characteristics, calibration, and decision curve analysis. The SHapley Additive exPlanations (SHAP) was utilized to explain the best-performing ML model.Results: A total of 147 IgAN patients were included in the study, with 103 in the training group and 44 in the test group .Among them, the US-SMI based XGBoost model achieved the best results, with an the area under the curve (AUC) of 0.839 (95% CI,0.756- 0.910) and an accuracy of 78.6% in the training group.In the test group, the AUC was 0.859 (95% CI,0.721- 0.964), and the accuracy was 81.8%, significantly surpassing the ML model of a single modality and the clinical model established based on occult blood. Additionally, the decision curve analysis (DCA) demonstrated that the XGBoost model provided a higher overall net benefit in the both groups.Conclusion: The SMI radiomics ML model has the capability to accurately predict the crescentic status of IgAN patients, providing effective assistance for clinical treatment decisions.Keywords: IgA nephropathy, crescent, ultrasound, superb microvascular imaging, radiomics